Peran Kawasan Ekonomi Khusus (KEK) terhadap Pertumbuhan Ekonomi Wilayah: Analisis Spasial Eksternalitas - Violita, Rizani; Khoirunurrofik, Khoirunurrofik (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study examines the impact of SEZs in Indonesia on regional economic growth, including impacts on neighbouring regencies and cities, using a Dynamic Spatial Durbin Model. The study indicates the impact of SEZs is only evident in tourism SEZs, while manufacturing SEZs have no discernible impact. The impact of SEZs on regional growth is transient. The significant variables are prior regional growth, Domestic Investment (PMDN), Labor Force Participation Rate (TPAK), Availability of Information and Communication Technology, Human Development Index (HDI), and GRDP growth. Influencing variables in the surrounding areas include GRDP growth and the diffusion of information and communication technologies.